Development and study of a monoclonal antibody to the human HLA-class II invariant chain - Veenstra, Hannelore F U (Department of Biological Sciences, 2024)
The work I present in this thesis was initiated by a request for a monoclonal antibody (MoAb) to the peripheral blood cells of a patient with chronic lymphocytic leukemia (CLL). It was initially hoped that such an antibody, if directed against an idiotypic determinant on the malignant B-cell surface, may prove to be useful therapeutically by virtue of its specificity and limited reactivity. At the time at which the request was made there had already been favourable reports of the use of MoAb's for the management of B-cell derived malignancies